Using QR-Coded Geometry Cards to Improve Elementary School Students' Mathematics Learning Outcomes - Tunjung Sabdarifanti; Fery Muhamad Firdaus; Setiawan Edi Wibowo (Universitas Pendidikan Ganesha, 2025)
Low mathematics learning outcomes and the lack of learning media are problems that should be considered. The purpose of this study is to create a QR coded geometry card learning media that is feasible, practical, and effective for learning mathematics on flat shapes. This study uses the R&D (Research and Development) research type with the ADDIE development method. The research was conducted at an elementary school involving grade II students. Data were collected through interviews, observations, media and material validation questionnaires, teacher and student response questionnaires, and learning outcome tests. The research data were analyzed using quantitative and qualitative analysis techniques. The results of the study showed that the media had been assessed as feasible by media experts and material experts with the criteria of